Model of organizational abilities among secondary school teachers - Dona Ningrum Mawardi; C. Asri Budiningsih; Sugiman Sugiman; Habibi Habibi (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study confirms the correlation model constructed among organizational abilities variables of secondary school teachers. The organizational abilities variables are: organizational commitment, and professional commitment, job satisfaction, and job performance. The samples are secondary school teachers selected using purposive sampling techniques. Data were collected through a rating scale questionnaire (1-5) and analyzed using Lisrel 8.0 program. The results show that professional commitment has a significant effect on organizational commitment and job satisfaction with values of 2.72 and 2.60. Other findings that organizational commitment and job satisfaction have an effect on job performance with values of 2.36 and 2.02. Empirically, the results concluded that the correlation among the variables theoretically fulfilled the fit criteria.